2008
DOI: 10.1177/0022185608089998
|View full text |Cite
|
Sign up to set email alerts
|

Major Tribunal Decisions in 2007

Abstract: Despite relatively low levels of industrial disputation in 2007, the AIRC delivered some significant decisions in relation to the 'genuine operational reasons' exclusion to the unfair dismissal jurisdiction, and secret ballots for protected industrial action. However, arguably the most significant decisions in 2007 came from the Supreme Court of New South Wales and the Federal Court of Australia. These decisions illustrate that the common law contract of employment provides (increasingly) robust protections to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…38 The facts upon which Russell was decided, and the causes of action with which it dealt, are set out in detail in 'Major Tribunal Decisions in 2007'. 39 They are not repeated here. It will suffice to say that Rothman J found that the Church had terminated Mr Russell's employment in breach of contract (having also breached the implied duties to act in good faith and of mutual trust and confidence), but that the heads of damage relied upon by Mr Russell were not available to him.…”
Section: Implied Duties To Act In Good Faith and Of Mutual Trust And mentioning
confidence: 99%
“…38 The facts upon which Russell was decided, and the causes of action with which it dealt, are set out in detail in 'Major Tribunal Decisions in 2007'. 39 They are not repeated here. It will suffice to say that Rothman J found that the Church had terminated Mr Russell's employment in breach of contract (having also breached the implied duties to act in good faith and of mutual trust and confidence), but that the heads of damage relied upon by Mr Russell were not available to him.…”
Section: Implied Duties To Act In Good Faith and Of Mutual Trust And mentioning
confidence: 99%